Preparation method of high-strength spherical lithium iron phosphate and application thereof

CN122940139APending Publication Date: 2026-10-20银贮(阜阳)科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611417925.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有球形磷酸铁锂通常由多个纳米级一次颗粒团聚形成微米级二次颗粒,一次颗粒之间主要依靠烧结形成的连接区域以及碳质材料维持结合,因此二次颗粒内部仍可能存在较多孔隙,一次颗粒之间的连接强度有限,导致球形二次颗粒的整体机械强度不足

Benefits of technology

(1)本发明在第一次烧结前引入第一碳源和石墨化催化剂,并在第一次烧结后进行气流粉碎,有利于形成导电性能较好的磷酸铁锂前驱体;随后将所述磷酸铁锂前驱体与第二碳源和助熔剂共同进行二次成球,并经第二次烧结形成球形二次颗粒,使一次颗粒之间形成较为紧密的连接结构,减少二次颗粒内部孔隙,提高球形磷酸铁锂的结构致密性和机械强度,同时有利于提高极片压实密度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a method for preparing high-strength spherical lithium iron phosphate and its application, relating to the field of lithium battery material preparation technology. The invention involves wet grinding, first spray drying, first sintering, and air jet milling of an iron source, lithium source, phosphorus source, first carbon source, and graphitization catalyst to obtain a lithium iron phosphate precursor. The precursor is then wet homogenized with a second carbon source and a flux, followed by a second spray drying to obtain a spherical secondary particle precursor, which is then sintered a second time to obtain high-strength spherical lithium iron phosphate. The amount of flux added is 0.1% to 0.3% of the mass of the lithium iron phosphate precursor. The obtained material is then dry-mixed with polytetrafluoroethylene and conductive carbon black, followed by air jet shearing of carbon nanotubes, and hot-pressed to obtain a dry electrode. This invention is beneficial for improving the mechanical strength of the spherical particles, the compaction performance of the electrode sheet, and the processing adaptability of the dry electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery material preparation technology, and in particular to a method for preparing high-strength spherical lithium iron phosphate and its application. Background Technology

[0002] Lithium iron phosphate (LFP) is a widely used cathode material for lithium-ion batteries, characterized by high safety, long cycle life, good thermal stability, and relatively low raw material cost. However, LFP materials have relatively low electronic conductivity and lithium-ion diffusion rate, and their particle morphology, particle size distribution, and particle packing state affect the material's compaction performance, electrode processing performance, and electrochemical performance. Especially in applications requiring increased electrode active material loading and energy density, improving the packing density and structural stability of LFP particles is a crucial issue to consider during the preparation of LFP cathode materials.

[0003] Previously, the mainstream strategy typically improved the particle morphology of lithium iron phosphate materials through spheroidization. Spherical or near-spherical particles have better flowability and packing properties, which helps reduce ineffective voids between particles, increase powder tap density and electrode compaction density, and improve material uniformity in subsequent processing such as mixing and film formation. However, existing spherical lithium iron phosphate particles are usually formed by the agglomeration of multiple nanoscale primary particles into micron-scale secondary particles. The bonding between primary particles mainly relies on the connection regions formed by sintering and carbonaceous materials. Therefore, there may still be many pores inside the secondary particles, and the connection strength between primary particles is limited, resulting in insufficient overall mechanical strength of the spherical secondary particles. During subsequent electrode processing and battery use, spherical secondary particles with insufficient mechanical strength are prone to local breakage or damage to the interparticle connection structure when subjected to mechanical actions such as mixing, shearing, and rolling, thereby disrupting the original dense packing state of the spherical particles. At the same time, insufficient connection of primary particles and high porosity within the secondary particles also increase the internal transport resistance and the inhomogeneity of interfacial reactions, affecting the compaction performance and electrochemical stability of the material.

[0004] Therefore, how to improve the bonding degree between primary particles and the mechanical strength of secondary particles while maintaining the good morphology and conductivity of lithium iron phosphate spherical secondary particles, and improve their adaptability to subsequent electrode processing, is an urgent problem to be solved. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing high-strength spherical lithium iron phosphate and its application. This method maintains the good morphology and conductivity of spherical secondary lithium iron phosphate particles while improving the bonding strength between primary particles and the mechanical strength of secondary particles, and enhancing their adaptability to subsequent electrode processing. To solve the above technical problems, the present invention provides the following technical solution: A first aspect of the present invention relates to a method for preparing high-strength spherical lithium iron phosphate, comprising the following steps: S1. The iron source, lithium source, phosphorus source, first carbon source and graphitization catalyst are mixed and wet-milled. The slurry obtained by milling is spray-dried for the first time and sintered for the first time under an inert atmosphere. The material obtained from the first sintering is pulverized by airflow to obtain the lithium iron phosphate precursor. S2. The lithium iron phosphate precursor, the second carbon source and the flux are added to water for wet homogenization to obtain a secondary pelletizing slurry. The secondary pelletizing slurry is then subjected to a second spray drying to obtain a spherical secondary particle precursor. S3. The spherical secondary particle precursor is sintered for the second time under an inert atmosphere to obtain high-strength spherical lithium iron phosphate. The amount of flux added is 0.1% to 0.3% of the mass of the lithium iron phosphate precursor.

[0006] Further, in step S1, the iron source, lithium source, and phosphorus source are mixed in a ratio of Li / Fe molar ratio of 1.02 to 1.05 and Fe / P molar ratio of 0.965 to 0.975. The iron source includes one or more of ferric phosphate dihydrate, ferric phosphate, ferric oxide, and ferric oxide; The lithium source includes one or more of lithium phosphate, lithium carbonate, lithium oxalate, and lithium dihydrogen phosphate. The phosphorus source includes one or more of iron phosphate, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate.

[0007] Further, in step S1, the first carbon source includes one or more of glucose, sucrose, tartaric acid, urea, citric acid, gluconic acid, and cellobiose, and the amount of the first carbon source added is 6% to 12% of the mass of the iron source; The graphitization catalyst includes one or more of ferrocene, cobalt dicene, titanium dicene, cobalt chloride, nickel chloride, chromium acetate, and titanium bromide, and the amount of graphitization catalyst added is 0.1% to 0.3% of the mass of the iron source.

[0008] Further, in step S1, the particle size D of the particles in the slurry obtained by wet grinding... 50 The particle size D of the particles obtained from the first spray drying is 100–300 nm.50 The size is 20–40 μm; The temperature of the first sintering is 700-800℃, and the holding time is 2-6 hours; The pressure of the air jet milling is 0.3–0.5 MPa, the classification frequency is 100–300 Hz, and the particle size D of the lithium iron phosphate precursor obtained after air jet milling is [not specified]. 50 The range is 0.5–1.5 μm.

[0009] Further, in step S2, the second carbon source includes one or more of polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, polyacrylonitrile, starch, water-soluble resin, water-soluble asphalt, and polydopamine, and the amount of the second carbon source added is 4% to 8% of the mass of the lithium iron phosphate precursor; The flux includes one or more of LiF, LiCl, Li2O, MgCl2, Li3PO4, K2CO3, and Al2O3; The solid content of the secondary pelletizing slurry is 50% to 80%; The particle size D of the spherical secondary particle precursor 50 It is 5–15 μm.

[0010] Furthermore, in step S3, the temperature of the second sintering is 600-700℃, and the holding time is 5-12h.

[0011] A second aspect of the present invention relates to the application of a high-strength spherical lithium iron phosphate in the preparation of a dry electrode, wherein the high-strength spherical lithium iron phosphate is prepared by any of the above preparation methods, and the high-strength spherical lithium iron phosphate, polytetrafluoroethylene and conductive carbon black are dry-mixed to obtain a first mixture; Carbon nanotubes were added to the first mixture and subjected to airflow shearing to obtain a dry electrode mixture; The dry electrode mixture is hot-pressed to obtain a dry electrode.

[0012] Furthermore, the amount of polytetrafluoroethylene added is 3% to 6% of the mass of the high-strength spherical lithium iron phosphate; The total amount of conductive carbon black and carbon nanotubes added is 5% of the mass of the high-strength spherical lithium iron phosphate, and the mass ratio of conductive carbon black to carbon nanotubes is 1:4 to 4:1.

[0013] Furthermore, the dry mixing is carried out using a high-speed mixer with a mixing linear velocity of 10–50 m / s and a mixing time of 1–4 h; The gas pressure for the airflow shearing treatment is 0.1–0.5 MPa, and the particle size D of the mixed agglomerates in the dry electrode mixture obtained after the airflow shearing treatment is... 50 It is 5–15 μm.

[0014] Furthermore, the hot pressing composite is performed using a hot pressing roller mill, with a roller temperature of 150–200°C, a hot pressing pressure of 100–200 MPa, a roller speed of 3–10 m / min, and the thickness of the resulting dry electrode is 90–120 μm.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention introduces a first carbon source and a graphitization catalyst before the first sintering, and performs air jet pulverization after the first sintering, which is beneficial to forming a lithium iron phosphate precursor with good conductivity; then the lithium iron phosphate precursor is combined with a second carbon source and a flux to form spherical secondary particles, and then sintered for the second time to form spherical secondary particles, so that the primary particles form a relatively tight connection structure, reduce the internal pores of the secondary particles, improve the structural compactness and mechanical strength of the spherical lithium iron phosphate, and at the same time, it is beneficial to improve the compaction density of the electrode.

[0016] (2) The present invention dry-mixes the obtained high-strength spherical lithium iron phosphate with polytetrafluoroethylene and conductive carbon black, then adds carbon nanotubes for airflow shearing, and then forms a dry electrode by hot pressing. By combining high-strength spherical particles with dry film formation process, the distribution of active materials, binder components and conductive components in the electrode is improved while maintaining the integrity of particle structure, which is beneficial to improving the molding stability and long-term cycle performance of dry electrode. Attached Figure Description

[0017] Figure 1 This is a flowchart illustrating the preparation process of the high-strength spherical lithium iron phosphate of the present invention. Figure 2 This is a scanning electron microscope image of the high-strength spherical lithium iron phosphate obtained in Embodiment 1 of the present invention; Figure 3 This is a cross-sectional scanning electron microscope image of the high-strength spherical lithium iron phosphate obtained in Embodiment 1 of the present invention; Figure 4 The image shows the cross-sectional EDS elemental distribution of the high-strength spherical lithium iron phosphate obtained in Embodiment 1 of the present invention. Figure 5 This is a scanning electron microscope image of the spherical lithium iron phosphate prepared in Comparative Example 1 of this invention. Figure 6 This is a cross-sectional scanning electron microscope image of the spherical lithium iron phosphate prepared in Comparative Example 1 of this invention. Figure 7 This is a cross-sectional EDS elemental distribution map of the spherical lithium iron phosphate prepared in Comparative Example 1 of this invention. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be described more clearly and completely below. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0019] In this invention, the Li / Fe molar ratio and Fe / P molar ratio are calculated based on the actual elemental content of each raw material, rather than solely on its ideal chemical formula. Due to the influence of the raw material preparation process and actual elemental composition, the measured Fe / P molar ratio of ferric phosphate raw material can be lower than the 1:1 ratio corresponding to the ideal chemical formula FePO4. For example, when ferric phosphate is used as both an iron source and a phosphorus source, the amounts of Fe and P are calculated based on the measured iron and phosphorus contents, respectively, and included in the total amount of Fe and P in the feeding system.

[0020] Unless otherwise stated, all solid contents mentioned in the examples are by mass percentage; all pressure units are in MPa; PTFE is polytetrafluoroethylene, CNT is carbon nanotubes, SUPER P is conductive carbon black, PVDF-5130 is polyvinylidene fluoride binder, SUPER Li is conductive agent, and NMP is N-methylpyrrolidone.

[0021] Example 1: This embodiment provides a method for preparing high-strength spherical lithium iron phosphate and its application in the preparation of dry electrodes. The method for preparing high-strength spherical lithium iron phosphate includes the following steps: Step S1: According to the Li / Fe molar ratio of 1.03 and the Fe / P molar ratio of 0.965, ferric phosphate dihydrate, lithium carbonate, glucose as the first carbon source and ferrocene as the graphitization catalyst are added to pure water and mixed. The amount of glucose added is 9% of the mass of the iron source and the amount of ferrocene added is 0.15% of the mass of the iron source.

[0022] The resulting mixture was wet-milled to reduce the particle size D of the slurry. 50 The particle size reached 150 nm; subsequently, the resulting slurry underwent a first spray drying process to control the particle size D of the spray-dried particles. 50 The particle size was 25 μm. The dried powder was subjected to a first sintering under a nitrogen atmosphere at 720℃ for 4 hours. After the first sintering, the resulting material was subjected to air jet milling at a pressure of 0.3 MPa and a classification frequency of 150 Hz to achieve the desired particle size D. 50 The thickness was increased to 1.0 μm, yielding the lithium iron phosphate precursor.

[0023] Step S2: The lithium iron phosphate precursor obtained in step S1, polyvinyl alcohol (polyvinyl alcohol) as the second carbon source, and LiF as a flux are added to pure water for wet homogenization. The amount of polyvinyl alcohol added is 4% of the mass of the lithium iron phosphate precursor, and the amount of LiF added is 0.3% of the mass of the lithium iron phosphate precursor. The solid content of the resulting secondary pelletizing slurry is 60%. The wet-homogenized secondary pelletizing slurry is then subjected to a second spray drying to control the particle size D of the resulting spherical secondary pellet precursor. 50 It is 8μm.

[0024] Step S3: The spherical secondary particle precursor obtained in step S2 is placed in a nitrogen atmosphere for a second sintering at a temperature of 650°C and a holding time of 10 hours to obtain high-strength spherical lithium iron phosphate.

[0025] An application of high-strength spherical lithium iron phosphate in the preparation of dry-process electrodes includes: dry mixing the high-strength spherical lithium iron phosphate obtained in step S3, PTFE, and SUPER P, wherein the amount of PTFE added is 5% of the mass of the high-strength spherical lithium iron phosphate, and the amount of SUPER P added is 2% of the mass of the high-strength spherical lithium iron phosphate. Dry mixing is performed using a high-speed mixer at a mixing linear velocity of 15 m / s for 2 hours to obtain a first mixture.

[0026] Add 3% by weight of high-strength spherical lithium iron phosphate CNTs to the first mixture, and subject it to airflow shearing treatment at a gas pressure of 0.15 MPa, controlling the particle size D of the resulting mixed agglomerates. 50 The thickness is 8μm, resulting in a dry electrode mixture.

[0027] The obtained dry electrode mixture was hot-pressed using a hot-press roller press. The hot-press roller temperature was 160℃, the hot-press pressure was 150MPa, and the roller speed was 3m / min, resulting in a dry electrode with a thickness of 95μm.

[0028] Example 2: This embodiment provides a method for preparing high-strength spherical lithium iron phosphate and its application in the preparation of dry electrodes. The method for preparing high-strength spherical lithium iron phosphate includes the following steps: Step S1: Iron phosphate, lithium oxalate, sucrose (as the first carbon source), and cobalt dicene (as the graphitization catalyst) are added to pure water and mixed according to a Li / Fe molar ratio of 1.025 and a Fe / P molar ratio of 0.968. The amount of sucrose added is 7.5% of the iron source mass, and the amount of cobalt dicene added is 0.15% of the iron source mass. The resulting mixture is then wet-milled to achieve a particle size D in the slurry. 50 The particle size reached 200 nm; subsequently, the resulting slurry underwent a first spray drying process to control the particle size D of the spray-dried particles.50 The particle size was 30 μm. The dried powder was subjected to a first sintering under a nitrogen atmosphere at 750℃ for 3 hours. After the first sintering, the resulting material was subjected to air jet milling at a pressure of 0.4 MPa and a classification frequency of 210 Hz to achieve the desired particle size D. 50 The thickness was reduced to 0.8 μm, yielding the lithium iron phosphate precursor.

[0029] Step S2: The lithium iron phosphate precursor obtained in step S1, polyvinylpyrrolidone (PVP) as the second carbon source, and Li3PO4 as a flux are added to pure water for wet homogenization. The amount of PPVD added is 6.5% of the mass of the lithium iron phosphate precursor, and the amount of Li3PO4 added is 0.2% of the mass of the lithium iron phosphate precursor. The solid content of the resulting secondary pelletizing slurry is 55%. The wet-homogenized secondary pelletizing slurry is then subjected to a second spray drying to control the particle size D of the resulting spherical secondary pellet precursor. 50 It is 10μm.

[0030] Step S3: The spherical secondary particle precursor obtained in step S2 is placed in a nitrogen atmosphere for a second sintering at a temperature of 680℃ and a holding time of 8h to obtain high-strength spherical lithium iron phosphate.

[0031] An application of high-strength spherical lithium iron phosphate in the preparation of dry electrodes includes: dry mixing the high-strength spherical lithium iron phosphate obtained in step S3, PTFE, and SUPER P, wherein the amount of PTFE added is 3% of the mass of the high-strength spherical lithium iron phosphate, and the amount of SUPER P added is 3% of the mass of the high-strength spherical lithium iron phosphate. Dry mixing is performed using a high-speed mixer at a mixing linear velocity of 20 m / s for 1.5 h to obtain a first mixture.

[0032] Add 2% by weight of high-strength spherical lithium iron phosphate CNTs to the first mixture, and subject it to gas shear treatment at a gas pressure of 0.3 MPa, controlling the particle size D of the resulting mixed agglomerates. 50 The thickness is 10 μm, resulting in a dry electrode mixture.

[0033] The obtained dry electrode mixture was hot-pressed using a hot-press roller press. The hot-press roller temperature was 180℃, the hot-press pressure was 120MPa, and the roller speed was 5m / min, resulting in a dry electrode with a thickness of 105μm.

[0034] Example 3: This embodiment provides a method for preparing high-strength spherical lithium iron phosphate and its application in the preparation of dry electrodes. The method for preparing high-strength spherical lithium iron phosphate includes the following steps: Step S1: Ferric phosphate dihydrate, lithium oxalate, citric acid (as the first carbon source), and chromium acetate (as the graphitization catalyst) are mixed in pure water according to a Li / Fe molar ratio of 1.04 and a Fe / P molar ratio of 0.972. The amount of citric acid added is 8% of the iron source mass, and the amount of chromium acetate added is 0.2% of the iron source mass. The resulting mixture is then wet-milled to achieve a particle size D in the slurry. 50 The particle size reached 180 nm; subsequently, the resulting slurry underwent a first spray drying process to control the particle size D of the spray-dried particles. 50 The particle size was 35 μm. The dried powder was subjected to a first sintering under a nitrogen atmosphere at 780℃ for 2 hours. After the first sintering, the resulting material was subjected to air jet milling at a pressure of 0.3 MPa and a classification frequency of 180 Hz to achieve the desired particle size D. 50 The thickness was increased to 1.2 μm, yielding the lithium iron phosphate precursor.

[0035] Step S2: The lithium iron phosphate precursor obtained in step S1, polyethylene glycol as the second carbon source, and Li2O as the flux are added to pure water for wet homogenization. The amount of polyethylene glycol added is 8% of the mass of the lithium iron phosphate precursor, and the amount of Li2O added is 0.1% of the mass of the lithium iron phosphate precursor. The solid content of the resulting secondary pelletizing slurry is 70%. The wet-homogenized secondary pelletizing slurry is then subjected to a second spray drying to control the particle size D of the resulting spherical secondary pellet precursor. 50 It is 6μm.

[0036] Step S3: The spherical secondary particle precursor obtained in step S2 is placed in a nitrogen atmosphere for a second sintering at a temperature of 620°C and a holding time of 8 hours to obtain high-strength spherical lithium iron phosphate.

[0037] An application of high-strength spherical lithium iron phosphate in the preparation of dry-process electrodes includes: dry mixing the high-strength spherical lithium iron phosphate obtained in step S3, PTFE, and SUPER P, wherein the amount of PTFE added is 4.5% of the mass of the high-strength spherical lithium iron phosphate, and the amount of SUPER P added is 4% of the mass of the high-strength spherical lithium iron phosphate. Dry mixing is performed using a high-speed mixer at a mixing linear velocity of 40 m / s for 1 hour to obtain a first mixture.

[0038] Add 1% by weight of high-strength spherical lithium iron phosphate CNTs to the first mixture, and subject it to airflow shearing treatment at a gas pressure of 0.25 MPa, controlling the particle size D of the resulting mixed agglomerates. 50 The thickness is 6μm, resulting in a dry electrode mixture.

[0039] The obtained dry electrode mixture was hot-pressed using a hot-press roller press. The hot-press roller temperature was 165℃, the hot-press pressure was 180MPa, and the roller speed was 7m / min, resulting in a dry electrode with a thickness of 98μm.

[0040] Example 4: This embodiment provides a method for preparing high-strength spherical lithium iron phosphate and its application in the preparation of dry electrodes. The method for preparing high-strength spherical lithium iron phosphate includes the following steps: Step S1: Ferric oxide, lithium carbonate, ammonium dihydrogen phosphate, urea as the first carbon source, and titanium diacene as the graphitization catalyst are added to pure water and mixed according to a Li / Fe molar ratio of 1.035 and a Fe / P molar ratio of 0.970. The amount of urea added is 6% of the iron source mass, and the amount of titanium diacene added is 0.3% of the iron source mass. The resulting mixture is then wet-milled to achieve a particle size D in the slurry. 50 The particle size reached 260 nm; subsequently, the resulting slurry underwent a first spray drying process to control the particle size D of the spray-dried particles. 50 The particle size was 20 μm. The dried powder was subjected to a first sintering under a nitrogen atmosphere at 760℃ for 5 hours. After the first sintering, the resulting material was subjected to air jet milling at a pressure of 0.5 MPa and a classification frequency of 260 Hz to achieve the desired particle size D. 50 The thickness was reduced to 0.5 μm, yielding the lithium iron phosphate precursor.

[0041] Step S2: The lithium iron phosphate precursor obtained in step S1, polydopamine as the second carbon source, and MgCl2 as a flux are added to pure water for wet homogenization. The amount of polydopamine added is 8% of the mass of the lithium iron phosphate precursor, and the amount of MgCl2 added is 0.25% of the mass of the lithium iron phosphate precursor. The solid content of the resulting secondary pelletizing slurry is 65%. The wet-homogenized secondary pelletizing slurry is then subjected to a second spray drying to control the particle size D of the resulting spherical secondary pellet precursor. 50 It is 11μm.

[0042] Step S3: The spherical secondary particle precursor obtained in step S2 is placed in a nitrogen atmosphere for a second sintering at a temperature of 620°C and a holding time of 8 hours to obtain high-strength spherical lithium iron phosphate.

[0043] An application of high-strength spherical lithium iron phosphate in the preparation of dry-process electrodes includes: dry mixing the high-strength spherical lithium iron phosphate obtained in step S3, PTFE, and SUPER P, wherein the amount of PTFE added is 4% of the mass of the high-strength spherical lithium iron phosphate, and the amount of SUPER P added is 1% of the mass of the high-strength spherical lithium iron phosphate. Dry mixing is performed using a high-speed mixer at a mixing linear velocity of 35 m / s for 3 hours to obtain a first mixture.

[0044] Add 4% by weight of high-strength spherical lithium iron phosphate CNTs to the first mixture, and subject it to airflow shearing treatment at a gas pressure of 0.4 MPa, controlling the particle size D of the resulting mixed agglomerates. 50 The thickness is 11 μm, resulting in a dry electrode mixture.

[0045] The obtained dry electrode mixture was hot-pressed using a hot-press roller press. The hot-press roller temperature was 190℃, the hot-press pressure was 160MPa, and the roller speed was 4m / min, resulting in a dry electrode with a thickness of 102μm.

[0046] Example 5: This embodiment provides a method for preparing high-strength spherical lithium iron phosphate and its application in the preparation of dry electrodes. The method for preparing high-strength spherical lithium iron phosphate includes the following steps: Step S1: According to a Li / Fe molar ratio of 1.045 and a Fe / P molar ratio of 0.965, ferric phosphate dihydrate, lithium dihydrogen phosphate, gluconic acid as the first carbon source, and cobalt chloride as the graphitization catalyst are added to pure water and mixed. The amount of gluconic acid added is 10% of the iron source mass, and the amount of cobalt chloride added is 0.26% of the iron source mass. The resulting mixture is then wet-milled to achieve a particle size D in the slurry. 50 The particle size reached 120 nm; subsequently, the resulting slurry underwent a first spray drying process to control the particle size D of the spray-dried particles. 50 The particle size was 35 μm. The dried powder was subjected to a first sintering under a nitrogen atmosphere at 775℃ for 4 hours. After the first sintering, the resulting material was subjected to air jet milling at a pressure of 0.3 MPa and a classification frequency of 200 Hz to achieve the desired particle size D. 50 The thickness was reduced to 0.7 μm, yielding the lithium iron phosphate precursor.

[0047] Step S2: The lithium iron phosphate precursor obtained in step S1, the water-soluble resin as the second carbon source, and LiCl as the flux are added to pure water for wet homogenization. The amount of water-soluble resin added is 6% of the mass of the lithium iron phosphate precursor, and the amount of LiCl added is 0.3% of the mass of the lithium iron phosphate precursor. The solid content of the resulting secondary pelletizing slurry is 75%. The wet-homogenized secondary pelletizing slurry is then subjected to a second spray drying to control the particle size D of the resulting spherical secondary pellet precursor. 50 It is 9μm.

[0048] Step S3: The spherical secondary particle precursor obtained in step S2 is placed in a nitrogen atmosphere for a second sintering at a temperature of 660℃ and a holding time of 12h to obtain high-strength spherical lithium iron phosphate.

[0049] An application of high-strength spherical lithium iron phosphate in the preparation of dry electrodes includes: dry mixing the high-strength spherical lithium iron phosphate obtained in step S3, PTFE, and SUPER P, wherein the amount of PTFE added is 6% of the mass of the high-strength spherical lithium iron phosphate, and the amount of SUPER P added is 2.5% of the mass of the high-strength spherical lithium iron phosphate. Dry mixing is performed using a high-speed mixer at a mixing linear velocity of 28 m / s for 1.5 h to obtain a first mixture.

[0050] High-strength spherical lithium iron phosphate CNTs (2.5% by mass) were added to the first mixture, and the mixture was subjected to gas shear treatment at a gas pressure of 0.35 MPa. The particle size D of the resulting mixed agglomerates was controlled. 50 The thickness is 9 μm, resulting in a dry electrode mixture.

[0051] The obtained dry electrode mixture was hot-pressed using a hot-press roller press. The hot-press roller temperature was 180℃, the hot-press pressure was 155MPa, and the roller speed was 6m / min, resulting in a dry electrode with a thickness of 115μm.

[0052] Example 6: This embodiment provides a method for preparing high-strength spherical lithium iron phosphate and its application in the preparation of dry electrodes. The method for preparing high-strength spherical lithium iron phosphate includes the following steps: Step S1: Iron(III) oxide, lithium carbonate, ammonium dihydrogen phosphate, tartaric acid (as the first carbon source), and titanium diacene (as the graphitization catalyst) are mixed in pure water according to a Li / Fe molar ratio of 1.05 and a Fe / P molar ratio of 0.975. The amount of tartaric acid added is 12% of the iron source mass, and the amount of titanium diacene added is 0.18% of the iron source mass. The resulting mixture is then wet-milled to achieve a particle size D in the slurry. 50 The particle size reached 235 nm; subsequently, the resulting slurry underwent a first spray drying process to control the particle size D of the spray-dried particles.50 The particle size was 40 μm. The dried powder was subjected to a first sintering under a nitrogen atmosphere at 725℃ for 6 hours. After the first sintering, the resulting material was subjected to air jet milling at a pressure of 0.45 MPa and a classification frequency of 250 Hz to achieve the desired particle size D. 50 The thickness was increased to 1.4 μm, yielding the lithium iron phosphate precursor.

[0053] Step S2: The lithium iron phosphate precursor obtained in step S1, water-soluble asphalt as the second carbon source, and Li3PO4 as a flux are added to pure water for wet homogenization. The amount of water-soluble asphalt added is 5% of the mass of the lithium iron phosphate precursor, and the amount of Li3PO4 added is 0.3% of the mass of the lithium iron phosphate precursor. The solid content of the resulting secondary pelletizing slurry is 65%. The wet-homogenized secondary pelletizing slurry is then subjected to a second spray drying to control the particle size D of the resulting spherical secondary pellet precursor. 50 It is 5μm.

[0054] Step S3: The spherical secondary particle precursor obtained in step S2 is placed in a nitrogen atmosphere for a second sintering at a temperature of 700℃ and a holding time of 8h to obtain high-strength spherical lithium iron phosphate.

[0055] An application of high-strength spherical lithium iron phosphate in the preparation of dry electrodes includes: dry mixing the high-strength spherical lithium iron phosphate obtained in step S3, PTFE, and SUPER P, wherein the amount of PTFE added is 3.5% of the mass of the high-strength spherical lithium iron phosphate, and the amount of SUPER P added is 3% of the mass of the high-strength spherical lithium iron phosphate. Dry mixing is performed using a high-speed mixer at a mixing linear velocity of 18 m / s for 4 hours to obtain a first mixture.

[0056] Add 2% (by weight) of high-strength spherical lithium iron phosphate CNTs to the first mixture, and subject it to airflow shearing treatment at a gas pressure of 0.5 MPa, controlling the particle size D of the resulting mixed agglomerates. 50 The thickness is 5μm, resulting in a dry electrode mixture.

[0057] The obtained dry electrode mixture was hot-pressed using a hot-press roller press. The hot-press roller temperature was 185℃, the hot-press pressure was 140MPa, and the roller speed was 8m / min, resulting in a dry electrode with a thickness of 98μm.

[0058] Example 7: This embodiment provides a method for preparing high-strength spherical lithium iron phosphate and its application in the preparation of dry electrodes. The method for preparing high-strength spherical lithium iron phosphate includes the following steps: Step S1: According to the Li / Fe molar ratio of 1.03 and the Fe / P molar ratio of 0.975, iron phosphate, lithium carbonate, citric acid as the first carbon source and nickel chloride as the graphitization catalyst are added to pure water and mixed. The amount of citric acid added is 10% of the mass of the iron source and the amount of nickel chloride added is 0.18% of the mass of the iron source.

[0059] The resulting mixture was wet-milled to reduce the particle size D of the slurry. 50 The particle size reached 215 nm; subsequently, the resulting slurry underwent a first spray drying process to control the particle size D of the spray-dried particles. 50 The particle size was 25 μm. The dried powder was subjected to a first sintering under a nitrogen atmosphere at 730℃ for 6 hours. After the first sintering, the resulting material was subjected to air jet milling at a pressure of 0.4 MPa and a classification frequency of 220 Hz to achieve the desired particle size D. 50 The thickness was increased to 1.1 μm, yielding the lithium iron phosphate precursor.

[0060] Step S2: The lithium iron phosphate precursor obtained in step S1, the water-soluble resin as the second carbon source, and K2CO3 as the flux are added to pure water for wet homogenization. The amount of water-soluble resin added is 5% of the mass of the lithium iron phosphate precursor, and the amount of K2CO3 added is 0.25% of the mass of the lithium iron phosphate precursor. The solid content of the resulting secondary pelletizing slurry is 80%. The wet-homogenized secondary pelletizing slurry is then subjected to a second spray drying to control the particle size D of the resulting spherical secondary pellet precursor. 50 It is 8μm.

[0061] Step S3: The spherical secondary particle precursor obtained in step S2 is placed in a nitrogen atmosphere for a second sintering at a temperature of 660℃ and a holding time of 10h to obtain high-strength spherical lithium iron phosphate.

[0062] An application of high-strength spherical lithium iron phosphate in the preparation of dry-process electrodes includes: dry mixing the high-strength spherical lithium iron phosphate obtained in step S3, PTFE, and SUPER P, wherein the amount of PTFE added is 5.5% of the mass of the high-strength spherical lithium iron phosphate, and the amount of SUPER P added is 2% of the mass of the high-strength spherical lithium iron phosphate. Dry mixing is performed using a high-speed mixer at a mixing linear velocity of 21 m / s for 3.5 h to obtain a first mixture.

[0063] Add 3% (by weight) of high-strength spherical lithium iron phosphate CNTs to the first mixture, and subject it to gas shear treatment at a gas pressure of 0.45 MPa, controlling the particle size D of the resulting mixed agglomerates. 50 The thickness is 8μm, resulting in a dry electrode mixture.

[0064] The obtained dry electrode mixture was hot-pressed using a hot-press roller press. The hot-press roller temperature was 180℃, the hot-press pressure was 135MPa, and the roller speed was 5m / min, resulting in a dry electrode with a thickness of 120μm.

[0065] Example 8: This embodiment provides a method for preparing high-strength spherical lithium iron phosphate and its application in the preparation of dry electrodes. The method for preparing high-strength spherical lithium iron phosphate includes the following steps: Step S1: Iron phosphate dihydrate, lithium carbonate, sucrose (as the first carbon source), and titanium bromide (as the graphitization catalyst) are added to pure water and mixed according to a Li / Fe molar ratio of 1.02 and a Fe / P molar ratio of 0.972. The amount of sucrose added is 8% of the iron source mass, and the amount of titanium bromide added is 0.15% of the iron source mass. The resulting mixture is then wet-milled to achieve a particle size D in the slurry. 50 The particle size reached 180 nm; subsequently, the resulting slurry underwent a first spray drying process to control the particle size D of the spray-dried particles. 50 The particle size was 30 μm. The dried powder was subjected to a first sintering under a nitrogen atmosphere at 725℃ for 6 hours. After the first sintering, the resulting material was subjected to air jet milling at a pressure of 0.35 MPa and a classification frequency of 210 Hz to achieve the desired particle size D. 50 The thickness was increased to 1.2 μm, yielding the lithium iron phosphate precursor.

[0066] Step S2: The lithium iron phosphate precursor obtained in step S1, polyvinylpyrrolidone (PVP) as the second carbon source, and Al2O3 as a flux are added to pure water for wet homogenization. The amount of PPVD added is 5% of the mass of the lithium iron phosphate precursor, and the amount of Al2O3 added is 0.20% of the mass of the lithium iron phosphate precursor. The solid content of the resulting secondary pelletizing slurry is 60%. The wet-homogenized secondary pelletizing slurry is then subjected to a second spray drying to control the particle size D of the resulting spherical secondary pellet precursor. 50 It is 6μm.

[0067] Step S3: The spherical secondary particle precursor obtained in step S2 is placed in a nitrogen atmosphere for a second sintering at a temperature of 680℃ and a holding time of 5h to obtain high-strength spherical lithium iron phosphate.

[0068] An application of high-strength spherical lithium iron phosphate in the preparation of dry-process electrodes includes: dry mixing the high-strength spherical lithium iron phosphate obtained in step S3, PTFE, and SUPER P, wherein the amount of PTFE added is 5% of the mass of the high-strength spherical lithium iron phosphate, and the amount of SUPER P added is 2.5% of the mass of the high-strength spherical lithium iron phosphate. Dry mixing is performed using a high-speed mixer at a mixing linear velocity of 18 m / s for 3 hours to obtain a first mixture.

[0069] High-strength spherical lithium iron phosphate CNTs (2.5% by mass) were added to the first mixture, and the mixture was subjected to gas shear treatment at a gas pressure of 0.35 MPa. The particle size D of the resulting mixed agglomerates was controlled. 50 The thickness is 6μm, resulting in a dry electrode mixture.

[0070] The obtained dry electrode mixture was hot-pressed using a hot-press roller press. The hot-press roller temperature was 200℃, the hot-press pressure was 145MPa, and the roller speed was 3m / min, resulting in a dry electrode with a thickness of 100μm.

[0071] Comparative Example 1: The lithium iron phosphate material and dry electrode were prepared according to the preparation method of Example 1, except that: the graphitization catalyst ferrocene was not added in step S1, and the fluxing agent LiF was not added in step S2.

[0072] Comparative Example 2: The preparation method was carried out according to Example 1, except that the graphitization catalyst ferrocene was not added in step S1.

[0073] Comparative Example 3: The preparation method of Example 1 was followed, except that no fluxing agent LiF was added in step S2.

[0074] Comparative Example 4: To evaluate the performance of the high-strength spherical lithium iron phosphate obtained in this invention using different electrode preparation routes, high-strength spherical lithium iron phosphate was prepared according to steps S1 to S3 of Example 1, and the electrode was prepared using a wet slurry preparation method. Specifically, the obtained high-strength spherical lithium iron phosphate, PVDF-5130, and SUPER Li were added to NMP at a mass ratio of 8:1:1 to form an electrode slurry with a solid content of 50%. After mixing, the slurry was coated, dried, and rolled. The coating thickness was 80 μm, the drying temperature was 105 °C, the drying time was 3 h, and the rolling pressure was 24 MPa to obtain a wet electrode.

[0075] Structural and morphological characterization: To characterize the particle morphology, internal structure, and elemental distribution of the lithium iron phosphate materials prepared in the examples and comparative examples, surface scanning electron microscopy, cross-sectional scanning electron microscopy, and cross-sectional EDS elemental distribution tests were performed on the lithium iron phosphate materials obtained in Example 1 and Comparative Example 1, respectively.

[0076] Depend on Figure 2 and Figure 5 It can be seen that the lithium iron phosphate obtained in both Example 1 and Comparative Example 1 forms spherical secondary particles. The spherical secondary particles obtained in Example 1 have a more complete overall morphology and a more dense particle surface structure; in contrast, the spherical secondary particles obtained in Comparative Example 1 have relatively obvious interparticle gaps on their surface.

[0077] Depend on Figure 3 and Figure 6 It can be seen that the primary particles inside the high-strength spherical lithium iron phosphate secondary particles obtained in Example 1 are arranged more densely, with relatively obvious connection regions between the primary particles and relatively few internal pores. In contrast, there are more gaps and pores between the primary particles inside the spherical lithium iron phosphate particles obtained in Comparative Example 1. This indicates that the preparation system of graphitization catalyst, two-stage carbon source and flux combined with secondary sintering used in this invention is beneficial to enhancing the degree of connection between primary particles and improving the density of the internal structure of the spherical secondary particles.

[0078] Depend on Figure 4 and Figure 7 The EDS test results show that the carbon element distribution in the high-strength spherical lithium iron phosphate obtained in Example 1 is relatively uniform, while the uniformity of carbon element distribution in the spherical lithium iron phosphate obtained in Comparative Example 1 is relatively poor. These results indicate that, based on the introduction of a two-stage carbon source, the combination of a graphitization catalyst and a flux is beneficial to improving the distribution of carbon components in spherical lithium iron phosphate particles.

[0079] Performance testing: To further evaluate the comprehensive performance of the lithium iron phosphate materials and electrodes obtained in Examples 1-8 and Comparative Examples 1-4, the carbon content, powder resistivity, electrode compaction density, crushing strength, and electrochemical performance of the samples obtained in each example and comparative example were tested. The carbon content, powder resistivity, electrode compaction density, and crushing strength were all determined using conventional testing methods in the art. Examples 1-8 and Comparative Examples 1-4 were all tested under the same conditions and methods, and the average values ​​of the obtained test data were taken.

[0080] For electrochemical performance testing, the electrodes obtained in Examples 1-8 and Comparative Examples 1-4 were assembled into CR2032 coin cell half-cells. The electrolyte was a 1 mol / L LiPF6 solution, and the solvent was a mixed solvent of EC, DMC, and EMC with a volume ratio of 1:1:1. The separator was a polypropylene membrane, and the negative electrode was a lithium metal sheet. The test voltage range was 2.0–3.75 V. The cells were charged to 3.75 V using a constant current and constant voltage method, and discharged to 2.0 V using a constant current method.

[0081] Charge-discharge tests were conducted at 25℃ using a 1C rate to obtain the 1C discharge capacity. Cycling performance tests were then performed at a 1C rate, and the capacity retention rate after 10,000 cycles was determined by the ratio of the discharge capacity at 10,000 cycles to the discharge capacity at 1 cycle. Further capacity tests were conducted at -20℃ using a 1C rate, and the low-temperature capacity retention rate was determined by the ratio of the 1C capacity at -20℃ to the 1C capacity at 25℃. The test results are shown in Table 1.

[0082] Table 1 Table 1 shows that the carbon content of the high-strength spherical lithium iron phosphate obtained in Examples 1-8 is at a similar level, but the powder resistivity is significantly lower than that of Comparative Examples 1 and 2 without the addition of graphitization catalyst. For example, the powder resistivity of Example 1 is 5.1 Ω·cm, while that of Comparative Examples 1 and 2 is 46.7 Ω·cm and 26.8 Ω·cm, respectively. This indicates that adding the first carbon source and graphitization catalyst to the first sintering system is beneficial to reducing the powder resistivity of the obtained lithium iron phosphate material.

[0083] Regarding the particle mechanical properties, the high-strength spherical lithium iron phosphate obtained in Examples 1-8 has a crushing strength of 230-235 MPa, while the crushing strength of the materials obtained in Comparative Examples 1-3 is 150-155 MPa. Specifically, Comparative Example 3, by omitting only the flux in step S2, has a crushing strength reduced to 152 MPa, while the electrode compaction density is reduced from 2.56 g / cm³ in Example 1. 3 Reduced to 2.29 g / cm³ 3 The results indicate that adding flux to the secondary spherical formation based on the participation of a second carbon source, and forming spherical secondary particles through a second sintering process, is beneficial for enhancing the bonding between primary particles, improving the mechanical strength of the spherical secondary particles, and further improving the electrode compaction performance.

[0084] In terms of electrochemical performance, the 1C discharge capacity of Examples 1-8 was 155.5-156.4 mAh / g, the capacity retention rate after 10,000 1C cycles was 88.9%-90.8%, and the 1C capacity retention rate at -20℃ was 86.6%-88.8%. Compared with Comparative Examples 1-3, the materials obtained in these examples exhibited better capacity retention performance under long-term cycling and low-temperature conditions.

[0085] Furthermore, Comparative Example 4 used the same high-strength spherical lithium iron phosphate as Example 1, and prepared the electrode using a wet slurry method. Its powder resistivity, compaction density, crushing strength, and 1C capacity were similar to those of Example 1. However, after 10,000 cycles at 1C, the capacity retention rate was 83.4%, lower than the 90.8% of Example 1. These results indicate that, using the same high-strength spherical lithium iron phosphate material, the dry electrode preparation route employed in this invention can achieve better long-term cycling performance, demonstrating the good adaptability of the high-strength spherical lithium iron phosphate to dry electrode processing and long-term cycling applications.

[0086] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.

Claims

1. A method for preparing high-strength spherical lithium iron phosphate, characterized in that, Includes the following steps: S1. The iron source, lithium source, phosphorus source, first carbon source and graphitization catalyst are mixed and wet-milled. The slurry obtained by milling is spray-dried for the first time and sintered for the first time under an inert atmosphere. The material obtained from the first sintering is pulverized by airflow to obtain the lithium iron phosphate precursor. S2. The lithium iron phosphate precursor, the second carbon source and the flux are added to water for wet homogenization to obtain a secondary pelletizing slurry. The secondary pelletizing slurry is then subjected to a second spray drying to obtain a spherical secondary particle precursor. S3. The spherical secondary particle precursor is sintered for the second time under an inert atmosphere to obtain high-strength spherical lithium iron phosphate. The amount of flux added is 0.1% to 0.3% of the mass of the lithium iron phosphate precursor.

2. The method for preparing high-strength spherical lithium iron phosphate according to claim 1, characterized in that, In step S1, the iron source, lithium source, and phosphorus source are mixed in a ratio of Li / Fe molar ratio of 1.02 to 1.05 and Fe / P molar ratio of 0.965 to 0.

975. The iron source includes one or more of ferric phosphate dihydrate, ferric phosphate, ferric oxide, and ferric oxide; The lithium source includes one or more of lithium phosphate, lithium carbonate, lithium oxalate, and lithium dihydrogen phosphate. The phosphorus source includes one or more of iron phosphate, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate.

3. The method for preparing high-strength spherical lithium iron phosphate according to claim 1, characterized in that, In step S1, the first carbon source includes one or more of glucose, sucrose, tartaric acid, urea, citric acid, gluconic acid, and cellobiose, and the amount of the first carbon source added is 6% to 12% of the mass of the iron source. The graphitization catalyst includes one or more of ferrocene, cobalt dicene, titanium dicene, cobalt chloride, nickel chloride, chromium acetate, and titanium bromide, and the amount of graphitization catalyst added is 0.1% to 0.3% of the mass of the iron source.

4. The method for preparing high-strength spherical lithium iron phosphate according to claim 1, characterized in that, In step S1, the particle size D of the particles in the slurry obtained by wet grinding is... 50 The particle size D of the particles obtained from the first spray drying is 100–300 nm. 50 The size is 20–40 μm; The temperature of the first sintering is 700-800℃, and the holding time is 2-6 hours; The pressure of the air jet milling is 0.3–0.5 MPa, the classification frequency is 100–300 Hz, and the particle size D of the lithium iron phosphate precursor obtained after air jet milling is [not specified]. 50 The range is 0.5–1.5 μm.

5. The method for preparing high-strength spherical lithium iron phosphate according to claim 1, characterized in that, In step S2, the second carbon source includes one or more of polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, polyacrylonitrile, starch, water-soluble resin, water-soluble asphalt, and polydopamine, and the amount of the second carbon source added is 4% to 8% of the mass of the lithium iron phosphate precursor. The flux includes one or more of LiF, LiCl, Li2O, MgCl2, Li3PO4, K2CO3, and Al2O3; The solid content of the secondary pelletizing slurry is 50% to 80%; The particle size D of the spherical secondary particle precursor 50 It is 5–15 μm.

6. The method for preparing high-strength spherical lithium iron phosphate according to claim 1, characterized in that, In step S3, the temperature of the second sintering is 600-700℃, and the holding time is 5-12h.

7. The application of a high-strength spherical lithium iron phosphate in the preparation of dry-process electrodes, characterized in that, High-strength spherical lithium iron phosphate is prepared by the preparation method according to any one of claims 1 to 6. The high-strength spherical lithium iron phosphate, polytetrafluoroethylene and conductive carbon black are dry-mixed to obtain a first mixture. Carbon nanotubes were added to the first mixture and subjected to airflow shearing to obtain a dry electrode mixture; The dry electrode mixture is hot-pressed to obtain a dry electrode.

8. The application according to claim 7, characterized in that, The amount of polytetrafluoroethylene added is 3% to 6% of the mass of the high-strength spherical lithium iron phosphate. The total amount of conductive carbon black and carbon nanotubes added is 5% of the mass of the high-strength spherical lithium iron phosphate, and the mass ratio of conductive carbon black to carbon nanotubes is 1:4 to 4:

1.

9. The application according to claim 7, characterized in that, The dry mixing is carried out using a high-speed mixer with a mixing linear velocity of 10–50 m / s and a mixing time of 1–4 h. The gas pressure for the airflow shearing treatment is 0.1–0.5 MPa, and the particle size D of the mixed agglomerates in the dry electrode mixture obtained after the airflow shearing treatment is... 50 It is 5–15 μm.

10. The application according to claim 7, characterized in that, The hot pressing composite is performed using a hot pressing roller mill. The hot pressing roller temperature is 150-200℃, the hot pressing pressure is 100-200MPa, the roller speed is 3-10m / min, and the thickness of the resulting dry electrode is 90-120μm.